Literatur Study: The Influence of Culture in The Effectiveness of Cross-Cultural Counseling - Aryanto, Erwin (Philosophiamundi, 2024)
The influence of culture in the success of cross-cultural counseling because culture determines the method of understanding individuals. Culture also influences counselling service techniques, which depend on ideology, regional origin and beliefs. Culture influences an individual’s perspective and behavioural patterns. Guidance and counselling with a cultural diversity approach are diverse, with the motto Bhineka Tunggal Ika. Cultural diversity challenges counsellors in implementing guidance and counselling activities based on a cultural approach. During the guidance and counselling process, a counsellor will not only meet clients with the same background and problems. As a counsellor, you must know the differences between yourself and your counselee. Counsellors must be aware that there is a theoretical quality in counselling. Counsellors must have the ability to develop skills. Later, the counsellor will meet with clients who have different backgrounds, characters, aspects of the problem and different thought patterns from each other. Understanding the counselee's background in depth will make it easier for a counsellor to solve problems experienced by the counselee even though they have a different background.